IMPLEMENTASI KEBIJAKAN PERDA SURABAYA NO 17 TAHUN 2003 DALAM MENGELOLA PEDAGANG KAKI LIMA YANG BERADA DI WILAYAH KECAMATAN SUKOLILO - Orwala, Ahmat Gulam (Universitas 17 Agustus 1945 Surabaya, 2016)
The existence of street vendors in the districts Sukolilo considered as a cause of trafficcongestion and disrupt the beauty of the city. In line with the government policy to managevendors. Originally selling at Sukolilo districts. The government relocated hawkers in placealready in sediakn by the government. The aim of this study is to describe and analyze policymanagement vendors, implementation of management policies street vendors, as well asfactors in the face in the implementation of policies to manage vendors, the districtssukolilo.penelitian kualittif this approach. Collection techniques used among others to use themethod of observation, interviews. Results from the study showed that the implementation ofthe policy of the district governments in managing vendors, the Sukolilo District has some ofthe factors determining the success and failure of a policy, the communication factor, thefactor of resources and factors of attitude and commitment.Keywords: Policy Implementation, Surabaya Regulation No. 17 of 2003, Merchants Street,District Sukolilo